2020
DOI: 10.1038/s41418-020-00693-9
|View full text |Cite
|
Sign up to set email alerts
|

E6-mediated activation of JNK drives EGFR signalling to promote proliferation and viral oncoprotein expression in cervical cancer

Abstract: Human papillomaviruses (HPV) are a major cause of malignancy worldwide, contributing to ~5% of all human cancers including almost all cases of cervical cancer and a growing number of ano-genital and oral cancers. HPV-induced malignancy is primarily driven by the viral oncogenes, E6 and E7, which manipulate host cellular pathways to increase cell proliferation and enhance cell survival, ultimately predisposing infected cells to malignant transformation. Consequently, a more detailed understanding of viral-host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 91 publications
2
68
0
Order By: Relevance
“…E6 also targets sorting nexin 27 (SNX27), utilizing the PDZ domain to dysregulate trafficking of proteins such as glucose transporter 1 (GLUT1), essential for glucose uptake, thus disrupting cellular homeostasis and proliferation [129]. Furthermore, our lab recently demonstrated that HR-HPV E6 proteins promote host cell proliferation and survival in a PBM-dependent manner via the activation of c-Jun N-terminal kinase 1/2 (JNK1/2) [130]. Taken together, these observations have led to the hypothesis that targeting of PDZ proteins contributes significantly to HPV-induced transformation [131].…”
Section: The E6 Oncoproteinmentioning
confidence: 99%
“…E6 also targets sorting nexin 27 (SNX27), utilizing the PDZ domain to dysregulate trafficking of proteins such as glucose transporter 1 (GLUT1), essential for glucose uptake, thus disrupting cellular homeostasis and proliferation [129]. Furthermore, our lab recently demonstrated that HR-HPV E6 proteins promote host cell proliferation and survival in a PBM-dependent manner via the activation of c-Jun N-terminal kinase 1/2 (JNK1/2) [130]. Taken together, these observations have led to the hypothesis that targeting of PDZ proteins contributes significantly to HPV-induced transformation [131].…”
Section: The E6 Oncoproteinmentioning
confidence: 99%
“…The direct effect of HPV oncogenes on the expression of different ECM components has been previously reported. A recent study demonstrated that c-Jun inhibition in HPV-transformed cell lines (HeLa and CasKi) was associated with lower metalloproteinases type 9 (MMP-9) mRNA expression levels [ 8 ]. Furthermore, Shiau and coworkers showed that HPV16 E6 induced MMP-2 and -9 mRNA expression levels through an IL-8 dependent pathway in H1299 cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that JNK1/2 phosphorylation is upregulated in primary keratinocytes transduced with HPV18 [75]. Moreover, a recent study found that HPV E6 induces JNK phosphorylation via the PDZ-binding motif, activating c-jun expression, thereby promoting proliferation and expression of viral oncoproteins through EGFR in cervical cancer [76].…”
Section: Pi3k/akt/mtormentioning
confidence: 99%